Thai literary traditions - Manat Chitakasem; International Conference on Thai Studies 1993 School of Oriental and African Studies). (Bangkok Institute of Thai Studies, Chulalongkorn University, 1995)
Fourteen papers on Thai literature presented at Fifth International Conference on Thai Studies held at School of Oriental and African Studies, University of London, July 1993.
Includes bibliographical references.
Keywords: Thai literature -- History and criticism -- Congresses